Sully - Eastwood, Clint, 1930-; Komarnicki, Todd; Hanks, Tom; Eckhart, Aaron; Linney, Laura; Mahaffey, Valerie; Harrington, Delphi, 1937-; O'Malley, Mike, 1966-; Sheridan, Jamey; Gunn, Anna, 1968-; McCallany, Holt; Sullenberger, Chesley, 1951-; et al. (Hollywood, CA : Warner Bros. Entertainment, 2016)
On Thursday, January 15th, 2009 Captain Chesley Sullenberger landed his plane on the Hudson River, saving the lives of all 155 aboard. However, an investigation was unfolding that threatened to destroy his reputation and his career. Includes bonus disc of special features: Sully Sullenberger, The man behind the miracle; Moment by moment, averting disaster on the Hudson; Neck deep in the Hudson, Shooting Sully.
DVD release of the 2016 motion picture.
Based on the book "Highest duty" by Chesley "Sully" Sullenberger and Jeffrey Zaslow.
Special features: Sully Sullenberger: the man behind the miracle, featurette; Moment by moment: averting disaster on the Hudson, featurette; Neck deep in the Hudson: shooting Sully, featurette.
Tom Hanks, Aaron Eckhart, Laura Linney, Valerie Mahaffey, Delphi Harrington, Mike O'Malley, Jamey Sheridan, Anna Gunn, Holt McCallany.
MPAA rating: PG-13; for some peril and brief strong language.
DVD, widescreen presentation, region 1; Dolby digital 5.1 surround.
Keywords: Sullenberger, Chesley, -- 1951- -- Film adaptations; Air pilots -- Drama; Lifesaving -- Drama; Hudson River (N.Y. and N.J.) -- Drama; Feature films; Biographical films; Film adaptations